Thymbra capitata essential oil has a significant antimicrobial activity against methicillin‐resistant Staphylococcus aureus pre‐formed biofilms. (8th March 2022) - Almeida, L.; Lopes, N.; Gaio, V.; Cavaleiro, C.; Salgueiro, L.; Silva, V.; Poeta, P.; Cerca, N.
Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) is a multidrug‐resistant opportunistic pathogen with a great ability to form biofilms. Herein, the antimicrobial potential of Thymbra capitata essential oil (EO) against MRSA biofilms was investigated. The determination of the minimum inhibitory concentration (MIC) and the minimum lethal concentration (MLC) of the T. capitata EO was first investigated on a group of clinical isolates from septicaemias, diabetic foot ulcers and osteomyelitis. Biofilms were incubated with the EO at the MLC and its anti‐biofilm potential was investigated. A strong antimicrobial activity was observed, with MIC and MLC values between 0·32 and 0·64 mg l −1 . However, the concentration of EO necessary for the eradication of planktonic cells was insufficient to significantly reduce the biofilm biomass of some isolates. Nevertheless, cell culturability and overall cellular metabolism was strongly reduced in all biofilms tested, only when the EO was tested. Contrary to the tested antibiotics, T. capitata EO showed a significant antimicrobial activity against MRSA biofilms, by reducing cellular metabolism and cellular culturability. Abstract : Significance and Impact of the Study: The rise of MRSA strains is becoming a serious problem, especially due to increasing antibiotic resistance. The utilization of natural products, such as essential oils, have been pointed out as alternative treatment strategies. This is the first study to demonstrate a high antimicrobial and anti‐biofilm activity of Thymbra capitata essential oil for the treatment of MRSA biofilm‐related infections.